Eco-friendly control of fusarium wilt in tomato: molecular docking and functional analysis of ZnO nanoparticles and biostimulants - Heikal, Yasmin M.; Albahi, Amal M.; Abdelmigid, Hala M.; Alyamani, Amal A.; Elshafey, Naglaa; Soliman, Hoda M.; Haroun, Samia A. (Frontiers in Plant Science, 2025)
In Solanum lycopersicum L. plant, Fusarium oxysporum is a fungal pathogen that leads to heavy tomato losses and severe wilting (FW). This investigation was planned to control F. oxysporum through some resistance inducers including salicylic acid (SA)(0, 0.4, 0.5, and 0.6 mM), humic acid (HA)(0, 50, 100, and 150 mg/L), zinc nanoparticles (ZnO-NPs) (0, 100, 250, and 500 mg/L) applications on 35 days- old of tomato plantlets and compared to the negative and positive controls. The selected Fusarium strain was identified at the molecular level using 18S rRNA analysis and assigned with accession number FO-A1 (OM321440). Their antifungal efficacy was demonstrated by the inhibition of F. oxysporum growth in vitro, improved plant growth under greenhouse conditions in vivo, increased antioxidant activity (TAC), total protein and carbohydrate levels, and phenolic content (TPC) inflicted by the fungus. The most effective treatment was 500 mg/L of ZnO-NPs, which reduced disease incidence to 65% and disease severity to 1.0, compared to the inoculated control. In addition to in silico investigations of biostimulants and ZnO-NPs against lanosterol 14-alpha-demethylase (CYP51), the principal target of antifungal agents, the binding affinities were determined to be -5.0 and -2.4 Kcal/mol for salicylic acid and humic acid, respectively. ZnO-NPs exhibited metal interaction with the amino acid residues of CYP51, with a binding energy of -2.19 Kcal/mol, indicating the inhibitory potential of biostimulants and ZnO-NPs. By integrating these state-of-the-art methods, this study enhances the existing body of knowledge in the field, addressing crucial gaps in sustainable disease management and offering alternatives to conventional approaches.